Government Preparation for Hoax Cases During the Covid-19 Pandemic to Preserve the Nation’s Unity and Cohesion (Universitas Negeri Semarang, 2022)
People accustomed to all daily activities outside the home appear to have developed a sense of boredom as a result of being forced to adhere to the government's stay-at-home policy. And, of course, this program quickly became a popular issue on social media with the hashtag #dirumahAja, with the expectation that all Indonesians would comprehend and understand how to assist the government in breaking the chain of transmission of the fatal corona virus, which is a new form of virus. There are numerous examples of how this covid-19 epidemic may create havoc and disrupt human existence, and it feels very real to everyone in this country. Throughout this pandemic, the government was compelled to enact policies sufficient to ensure the nation's safety, and the hope that the national crisis would stop soon has become a global issue. Previously, if you encountered hoax news or news that was still confusing, you could immediately report it to the local police and face punishment for violating the ITE law. However, during this pandemic, and in relation to the pandemic issue that resulted in the emergence of HOAX news, it was not only the government that became the cause of this. enraged. But also among public people who turned out to be socially acceptable parties. This study used a qualitative descriptive technique to analyze life-affirming policies during the COVID-19 epidemic, which has caused widespread concern in all spheres of life.